2(3.5p+7)=7(p+1)

Simple and best practice solution for 2(3.5p+7)=7(p+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3.5p+7)=7(p+1) equation:


2(3.5p+7)=7(p+1)

We simplify the equation to the form, which is simple to understand
2(3.5p+7)=7(p+1)

Reorder the terms in parentheses
+(+7p+14)=7*(p+1)

Remove unnecessary parentheses
+7p+14=+7+*(+p+1+)

Reorder the terms in parentheses
+7p+14=+(+7p+7)

Remove unnecessary parentheses
+7p+14=+7p+7

We move all terms containing p to the left and all other terms to the right.
+7p-7p=+7-14

We simplify left and right side of the equation.
p=-7

0=-7

The left and right sides are not equal, therefore there is no solution. This equation is invalid.

See similar equations:

| 6x+5=10x+40 | | 6x+5=10x+20 | | 15/42.625-2=7/22.625+13/4 | | 4.39=-1.6c+7.59 | | 4x+6+2y+8=142 | | -7n-2=16 | | y^2-6y-5x=-14 | | -0.21=log(x) | | 20+130+p=180 | | 4t+17=7+5f | | 25x^3-10x= | | x^4+4x^2+1=0 | | X=y^2-6 | | -8(2-x)=416 | | 3x+2=96 | | (x-2)squared=50 | | (x^3+x^2+x+1)(13x-9)= | | 6k-16=2k+4 | | (x^4-x^2-2x+6)=0 | | (8-6i)-4=x-(1+yi) | | -3(2p+14)-28=2(p+15)+12 | | 6x-3=4(x+22) | | -11+4n=5-(11+17) | | (x^3-x^2-2)=0 | | .7(-3X-2)=3.5+1 | | -11+4n=5-(11+12) | | 6x+-10=110 | | 5x(x^3-x^2-2)=0 | | 20+2.50(19)=x | | 20+2.50(20)=x | | 20+2.50(18)=x | | 20+30+p=180 |

Equations solver categories